Transcriptional Inhibitors Identified in a 160, 000-Compound Small-Molecule DUX4 Viability Screen. (August 2016) - Choi, Si Ho; Bosnakovski, Darko; Strasser, Jessica M.; Toso, Erik A.; Walters, Michael A.; Kyba, Michael
Facioscapulohumeral muscular dystrophy is a genetically dominant, currently untreatable muscular dystrophy. It is caused by mutations that enable expression of the normally silent DUX4 gene, which encodes a pathogenic transcription factor. A screen based on Tet-on DUX4 -induced mouse myoblast death previously uncovered compounds from a 44, 000-compound library that protect against DUX4 toxicity. Many of those compounds acted downstream of DUX4 in an oxidative stress pathway. Here, we extend this screen to an additional 160, 000 compounds and, using greater stringency, identify a new set of DUX4-protective compounds. From 640 hits, we performed secondary screens, repurchased 46 of the most desirable, confirmed activity, and tested each for activity against other cell death–inducing insults. The majority of these compounds also protected against oxidative stress. Of the 100 repurchased compounds identified through both screens, only SHC40, 75, and 98 inhibited DUX4 target genes, but they also inhibited dox-mediated DUX4 expression. Using a target gene readout on the 640-compound hit set, we discovered three overlooked compounds, SHC351, 540, and 572, that inhibit DUX4 target gene upregulation without nonspecific effects on the Tet-on system. These novel inhibitors of DUX4 transcriptional activity may thus act on pathways or cofactors needed by DUX4 for transcriptional activation in these cells.